2020
DOI: 10.1186/s12936-020-03397-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the colorimetric malachite green loop-mediated isothermal amplification (MG-LAMP) assay for the detection of malaria species at two different health facilities in a malaria endemic area of western Kenya

Abstract: Background Prompt diagnosis and effective malaria treatment is a key strategy in malaria control. However, the recommended diagnostic methods, microscopy and rapid diagnostic tests (RDTs), are not supported by robust quality assurance systems in endemic areas. This study compared the performance of routine RDTs and smear microscopy with a simple molecular-based colorimetric loop-mediated isothermal amplification (LAMP) at two different levels of the health care system in a malaria-endemic area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Focusing in MaG, its low cost, color stability, simplicity of use, and storage are among its advantages over other dyes (Scott et al, 2020). The typical concentration ranges between 0.004% and 0.008% (Nzelu et al, 2014), and this dye seems to have found its niche in LAMP assays targeting different types of parasites (Barazorda et al, 2020;Chahar et al, 2018;Gachugia et al, 2020;Kamber et al, 2020;Lucchi et al, 2016;Nzelu et al, 2016Nzelu et al, , 2019Takagi et al, 2016), even though other pathogens have also been detected, such as bacteria (Cheng et al, 2020;Jothikumar et al, 2014;Li et al, 2019;Li, Liu, et al, 2020). Moving to MeG, it was reported to allow for clear color differentiation when added at a final concentration of 0.004%, and attending to a study from Thapa et al, dealing with the detection of M. tuberculosis, MeG developed the color change in the same time frame as of MaG but with a superior color intensity (Thapa et al, 2019).…”
Section: Crystal Violetmentioning
confidence: 99%
“…Focusing in MaG, its low cost, color stability, simplicity of use, and storage are among its advantages over other dyes (Scott et al, 2020). The typical concentration ranges between 0.004% and 0.008% (Nzelu et al, 2014), and this dye seems to have found its niche in LAMP assays targeting different types of parasites (Barazorda et al, 2020;Chahar et al, 2018;Gachugia et al, 2020;Kamber et al, 2020;Lucchi et al, 2016;Nzelu et al, 2016Nzelu et al, , 2019Takagi et al, 2016), even though other pathogens have also been detected, such as bacteria (Cheng et al, 2020;Jothikumar et al, 2014;Li et al, 2019;Li, Liu, et al, 2020). Moving to MeG, it was reported to allow for clear color differentiation when added at a final concentration of 0.004%, and attending to a study from Thapa et al, dealing with the detection of M. tuberculosis, MeG developed the color change in the same time frame as of MaG but with a superior color intensity (Thapa et al, 2019).…”
Section: Crystal Violetmentioning
confidence: 99%
“…Despite breakthroughs in malaria control, the illness has long been a major public health burden globally [ 1 ]. It, along with hepatitis, TB, and HIV/AIDS, has claimed many lives globally and is calamitous [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…During amplification reaction, high amounts of DNA and pyrophosphate ion by-product are produced, 24 allowing different ways of detection of amplified products, such as turbidity, fluorescence, or colorimetric dyes. 25,26 This flexibility in the way of detection besides the isothermal nature of the process, which does not require a thermocycler or highly specific devices, have supported LAMP method such as an useful tool to be performed in low resource settings for malaria detection. [26][27][28] In addition, some commercial LAMP methods for malaria diagnosis have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 This flexibility in the way of detection besides the isothermal nature of the process, which does not require a thermocycler or highly specific devices, have supported LAMP method such as an useful tool to be performed in low resource settings for malaria detection. [26][27][28] In addition, some commercial LAMP methods for malaria diagnosis have been developed. [29][30][31] Nevertheless, contamination can be also present in LAMP methods 31 and independent amplification processes are needed for species identification.…”
Section: Introductionmentioning
confidence: 99%